Faktor–Faktor yang Mempengaruhi Kemandirian Anak Retardasi Mental di SLBN 1 Padang - Miswarti Miswarti; Metha kemala Rahayu; Hasmita Hasmita; Jufrika Gusni (Lembaga Pengembangan Kinerja Dosen, 2024)
Problems that occur in children with mental retardation are weakness or inability in children accompanied by limited ability to fulfill independence. Support and acceptance from each family member will provide energy and confidence in mentally retarded children to make more efforts to improve every ability they have. Based on data obtained from the Social Service of West Sumatra Province (2020) there were 10,390 people with mental retardation. The purpose of the study was to determine the factors related to the independence of mentally retarded children at SLBN 1 Padang in 2024. The type of research is descriptive analytical with a cross sectional study design carried out at SLBN 1 Padang from Januari to April 2024. The population in this study were parents who cared for mentally retarded children at SLB N 1 Padang totaling 70 parents. The data is processed by editing, entry, coding and cleaning steps. Univariate analysis with frequency distribution and bivariate analysis with Chi Square statistical test with 95% confidence level. The results showed that 52.5% of children with mental retardation with less independence, 37.5% with poor knowledge, 56.3% with poor attitudes, 55.0% with poor family support. There is a significant relationship between attitude and children's independence (p-value = 0.000), between family support and children's independence (p-value = 0.048), and there is no relationship between parental knowledge and children's independence. (p-value = 0.083 ). Someone with a high attitude, knowledge, and family support will be more successful in dealing with and overcoming the problem compared to someone who receives a low attitude, knowledge, and family support. It is hoped that teachers and families will be able to provide examples of independent behavior that can be applied by students, both at home and at school.